2009
DOI: 10.3171/2008.9.jns08191
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, clinical manifestations, and course of water and electrolyte metabolism disturbances following transsphenoidal pituitary adenoma surgery: a prospective observational study

Abstract: Water and electrolyte disturbances occurred in the majority of patients undergoing transsphenoidal adenomectomy and were usually transient. Diabetes insipidus is more frequent than hyponatremia. Diabetes insipidus usually occurs during the 1st postoperative day and resolves in the majority of cases within 10 days. In few patients, DI may persist and require therapy with ADH analogs. Hyponatremia usually occurs at the end of the 1st postoperative week and resolves in most cases within 5 days. Very few patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 17 publications
9
107
1
4
Order By: Relevance
“…3 Following surgery in the pituitary region, the sequential occurrence of CSW and SIADH has been previously demonstrated to occur in the same patient. 5,12,18 However, fluctuations in serum sodium levels resulting in sequential development of hypernatremia and hyponatremia have not been previously described following HH surgery; this entity is in line with other water electrolyte disturbances experienced after surgery in this region.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…3 Following surgery in the pituitary region, the sequential occurrence of CSW and SIADH has been previously demonstrated to occur in the same patient. 5,12,18 However, fluctuations in serum sodium levels resulting in sequential development of hypernatremia and hyponatremia have not been previously described following HH surgery; this entity is in line with other water electrolyte disturbances experienced after surgery in this region.…”
mentioning
confidence: 66%
“…16 These authors suggested, as did others, that leakage of vasopressin from damaged hypothalamiconeurohypophysial tracts and the posterior pituitary causes an "isolated second phase" (hyponatremia). 5,16 In other studies, hyponatremia has been previously shown not to be associated with high levels of ADH but rather associated with elevated ANP, thought to have a role in CSW, after pituitary region surgery. 12,18 What likely happened in these 4 patients after resection of these very large tumors, most of which were removed aggressively, is a similar occurrence to the triphasic response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Surgery and tumors of supraoptic and paraventricular nuclear region can also be the cause of CDI. 14,15 CDI can also be due to the congenitally inherited mutations of prepro-vasopressin-neurophysin II gene involving the substitution of glycine for valine. 16 The other causes are autoimmunity, histocytosis, granulomatosis, sarcodosis and alcohol.…”
Section: Etiologymentioning
confidence: 99%